Utilizing Colpocleisis to Repair a Vesicovaginal Fistula in a Cervical Cancer Patient with History of Pelvic Radiation: A Case Report and Literature Review - Ahmad Dahman; Daniel McClelland; Stanley Zaslau; Valerie Galvan Turner; Omar Duenas; Robert Shapiro (Case Reports in Urology)
Background. Vesicovaginal fistula is a rare and distressing urological condition. It is especially prevalent in developing countries with the predominant etiology secondary to obstructed labor. Radiation therapy in female patients with cervical cancer is a risk factor for vesicovaginal fistula formation in the United States. Case Presentation. A 53-year-old woman with a history of cervical cancer and radiation presented with continuous urinary incontinence. Following diagnostic vaginoscopy, a 1 cm vesicovaginal fistula was diagnosed at the vaginal apex. The patient elected for surgical repair. She subsequently underwent successful transvaginal fistula closure using colpocleisis to optimally address the systemic factors of poor wound healing associated with irradiated tissue. Because of the adjacent tissue having been compromised by pelvic radiation, we opted to use a biologic graft made of human cadaveric pericardial tissue (CPT) instead of a native tissue flap to provide additional support for the fistula repair. Conclusion. A transvaginal approach for surgical repair of vesicovaginal fistula can be successful in patients with a prior history of pelvic radiation. Transvaginal colpocleisis is a viable option to augment vesicovaginal fistula repair for patients with significant comorbidities when sexual intercourse is no longer desired.